Isolation of alkaloids from Alseodaphne pendulifolia Gamd. (Lauraceae) and their biological activities - Muhammad Hafiz Husna Hasnan (Tanjong Malim, 2014)
Isolation of alkaloids from Alseodaphne pendulifolia Gamd. (Lauraceae) and their biological activities by Muhammad Hafiz Husna Hasnan